Meso-institutions shaping arenas for policymaking: an exploratory study on front-of-package food labelling in Brazil, Chile, and Mexico - Guerreiro, Felipe Jannuzzi; Vinholis, Marcela de Mello Brandão; Nunes, Rubens; Silva, Vivian Lara (Frontiers in Sustainable Food Systems, 2024)
Front-of-package food labelling (FOPL) is a mechanism to inform consumers on food nutrients content and risks for health. Each country, within its own institutional framework, defines methods and protocols to formulate rules capable of influencing organizations and the behavior of agents. The paper aims at evaluating the role of some meso-institutions in shaping arenas for policymaking on FOPL based on an exploratory study in Brazil, Chile, and Mexico. A documental analysis and literature review were employed, followed by in-depth interviews. The relevant aspects of FOPL assessed were thresholds for sugar, fats, and sodium; marketing restrictions, and timeframe given for compliance with the new rules. The contribution of this article is to illuminate the way in which meso-institutions operate in a specific context, namely the development of food labelling standards. The focus is to find the rules that allowed the participation of stakeholders in the process of defining normative acts intended to regulate food labelling. The discussion of mandatory FOPL can be interpreted as a struggle to define proper rights for the food industry and the consumer. Meso-institutions, as translators of general normative principles in specific contexts, can encourage or restrict stakeholder participation in policymaking. Besides political arena, the participation can be done in other arenas, such as legislature, regulatory agencies, scientific community, media and public opinion. Institutions that encourage stakeholder participation increase the probability of obtaining widely accepted specific rules.